Answer:
First you can find the rate of change to be 4.25. Then you can subtract 4.25 repeatedly until you get to an output with an input of zero. The initial value is the output when the input is zero. The initial value after subtracting 4.25 three times is 29.50.
Because the inputs go by 2, the rate of change is half the difference of the outputs, or 4.25. Subtract 4.25 repeatedly 3 times to get to an output with an input of 0. Calculate 42.25 – (3 x 4.25). The initial value is 29.50.
Hope this Helps!
The formula for the value of nth term is
= 3n + 1
Step-by-step explanation:
The formula of the nth term in the arithmetic sequence is
, where
- a is the first term of the sequence
- d is the common difference between each two consecutive terms
∵ The first term of an arithmetic sequence is equal to four
∴ a = 4
∵ The common difference is equal to three
∴ d = 3
- Substitute these values in the rule of the nth term
∵ ![a_{n}=a+(n-1)d](https://tex.z-dn.net/?f=a_%7Bn%7D%3Da%2B%28n-1%29d)
∴ ![a_{n}=4+(n-1)3](https://tex.z-dn.net/?f=a_%7Bn%7D%3D4%2B%28n-1%293)
- Simplify it
∴ ![a_{n}=4+3n-3](https://tex.z-dn.net/?f=a_%7Bn%7D%3D4%2B3n-3)
∴ ![a_{n}=1+3n](https://tex.z-dn.net/?f=a_%7Bn%7D%3D1%2B3n)
The formula for the value of nth term is
= 3n + 1
Learn more:
You can learn more about the sequence in brainly.com/question/7221312
#LearnwithBrainly
The correct answer is C (-20) let me know if you want to know how I got that answer
3x + 7 = -x - 1
3x + 7 + = -1
4x + 7 = -1
4x = -1 - 7
4x = -8
x = -2
1 - 2x + 5 = 4x - 3
-2x + 6 = 4x - 3
6 = 4x - 3 + 2x
6 = 6x - 3
6 + 3 = 6x
9 = 6x
x = 6/9
x = 2/3
i helped you with the first two questions so you can see how you can solve it.
hope this helps, God bless!
Lou has 800 pennies
Joe has 8 pennies
Therefore they have 808 pennies